Monogenic etiologies in a cohort of early onset obesity: a real-world experience from Belgium - Harvengt, Julie; Hannon, Muriel; Palmeira, Leonor; Lebrethon, Marie-Christine; Dideberg, Vinciane; Bours, Vincent (Frontiers in Endocrinology, 2025)
IntroductionObesity is a major global health issue with multifactorial etiologies. Among them, recent advances in the comprehension of eating and energy regulation showed that around 60 genes involved in the hypothalamic leptin/melanocortin pathway contribute to the development of rare monogenic or syndromic forms of obesity.ObjectiveTo better delineate the genetic diagnostic rate and the phenotype in a cohort of early onset obesity and to integrate our results in guidance for genetic testing.MethodsIn a diagnostic setting, 223 patients with early onset obesity were screened through a targeted panel including 44 genes for severe early onset obesity. Genetic results and clinical descriptions were reviewed for the entire cohort.ResultsA diagnostic yield of 3.1% was established. Likely pathogenic or pathogenic variants were found in MRAP2, MC4R, BBS2, and BBS4, and a 16p11.2 deletion was confirmed. Clinically, 23% of the cohort had early onset obesity at <1 year, 47% at 1–4 years, and 30% at >4 years. No discriminative clinical feature appears to enhance the diagnostic yield. Thirty-six percent of the cohort presented additional neurological complaints that led to more extensive genetic investigations with a diagnosis rate of 1.8% in this subgroup.ConclusionOur work found a diagnostic yield of 3.1%. Additionally, 19.7% of heterozygous variants of unknown significance were found in genes related to autosomal conditions and 34.9% in genes related to recessive conditions. These results highlight the need for accurate genotype-phenotype correlations. Genetic laboratory expertise in obesity is highly recommended, especially in the context of the availability of new targeted anti-obesity therapies that open the field for current and future perspectives of these targeted genetic investigations.